Efficient ways to combat doping in a sports education context!? A systematic review on doping prevention measures focusing on young age groups - Pöppel, K. (Frontiers in Sports and Active Living, 2021)
Youth is characterized by testing and crossing natural boundaries, sometimes with the help of performance-enhancing substances. In this context, doping prevention measures play a crucial role to protect individuals both within and outside the context of elite sport. Based on the PRISMA guidelines, a systematic literature search was conducted in the databases ProQuest (ERIC), Scopus, PSYNDEX/PsychInfo, PubMed, and Web of Science Core Collection to provide an overview of the impact of doping prevention measures, with particular attention to the underlying understanding of learning. As a result of the screening process, 30 of the initial 5,591 articles met the previously defined and recorded eligibility criteria. The analysis led to heterogeneous results regarding content, implementation, target group, or outcome variables considered relevant. Two-thirds of the studies related to the competitive sports context. Nevertheless, there has been a growing interest in studying doping prevention and its effects on non-elite athlete target groups in recent years. In terms of effectiveness, many measures did not achieve long-term changes or did not collect any follow-up data. This contrasts with understanding learning as sustained change and reduces the intended long-term protection of prevention measures, especially for adolescent target groups. Even young age groups from 10 years upwards benefited from doping prevention measures, and almost all doping prevention measures enabled their participants to increase their physical and health literacy. No conclusion can be drawn as to whether doping prevention measures based on constructivist ideas are superior to cognitivist approaches or a combination of both. Nevertheless, programs that actively engage their participants appear superior to lecture-based knowledge transfer. Most of the prevention measures offered a benefit-orientation so that participants can achieve added value, besides trying to initiate health-promoting change through rejection. Because of the lack of sustained changes, a further modification in doping prevention seems necessary. The review results support the value of primary prevention. Doping prevention measures should enable tailored learning and development options in the sense of more meaningful differentiation to individual needs. The implementation in a school context or an online setting is promising and sees doping as a problem for society. The review highlights the importance of accompanying evaluation measures to identify efficient prevention components that promote health and protect young people.